Cyberspace is used, first and foremost, to wage wars: proliferation, security and stability in cyberspace. Issue 1 (2nd January 2021) - Douzet, Frédérick; Gery, Aude
ABSTRACT: Cyberspace has completely revolutionised our ways of life, disrupted our economies, and allowed for important progress in our societies. But the advantages of the digital revolution are now threatened by the use of cyberspace for war purposes. This article explores the states' security dilemma as they face cyber challenges and the ambivalence of the notion of security in cyberspace. It highlights how, in ten years, cyberspace has become a battlefield and a strategic priority for many states that have represented it as a geopolitical threat for their national security, hence justifying its progressive militarisation. Meanwhile, they have become cognizant to the systemic risk of proliferation of offensive cybertools and cyber-operations. This security dilemma – one that opposes a representation of cyber threats as a geopolitical risk to that of cyberspace as a systemic risk – is at the heart of the multilateral negotiations on the regulation of cyberspace. There, a multiplicity of non-state actors has forced their way to the table through a multitude of initiatives that emphasize the importance of the challenges at stake and how difficult it will be for the states to face them.